A Novel Candidate Gene Associated With Body Weight in the Pacific White Shrimp Litopenaeus vannamei - Wang, Quanchao; Yu, Yang; Zhang, Qian; Zhang, Xiaojun; Yuan, Jianbo; Huang, Hao; Xiang, Jianhai; Li, Fuhua (Frontiers in Genetics, 2019)
Improvements of growth traits are always the focus in selective breeding programs for the Pacific white shrimp Litopenaeus vannamei (L. vannamei). Identification of growth-related genes or markers can contribute to the application of modern breeding technologies, and thus accelerate the genetic improvement of growth traits. The aim of this study was to identify the genes and molecular markers associated with the growth traits of L. vannamei. A population of 200 individuals was genotyped using 2b-RAD techniques for genome-wide linkage disequilibrium (LD) analysis and genome-wide association study (GWAS). The results showed that the LD decayed fast in the studied population, which suggest that it is feasible to fine map the growth-related genes with GWAS in L. vannamei. One gene designated as LvSRC, encoding the class C scavenger receptor (SRC), was identified as a growth-related candidate gene by GWAS. Further targeted sequencing of the candidate gene in another population of 322 shrimps revealed that several nonsynonymous mutations within LvSRC were significantly associated with the body weight (P < 0.01), and the most significant marker (SRC_24) located in the candidate gene could explain 13% of phenotypic variance. The current results provide not only molecular markers for genetic improvement in L. vannamei, but also new insights for understanding the growth regulation mechanism in penaeid shrimp.